Influence of surface state on hydrogen sorption by zirconium alloy Zr1Nb; AIP Conference Proceedings; Vol. 1772 : Prospects of Fundamental Sciences Development (PFSD-2016) - Kudiyarov V. N. Victor Nikolaevich; Babikhina (Babihina) M. N. Mariya Nikolaevna; Pushilina N. S. Natalia Sergeevna; Kashkarov E. B. Egor Borisovich; Syrtanov M. S. Maksim Sergeevich (Materials structure and properties under modification, 2016)
Title screen